CO2 Overall Splitting by a Bifunctional Metal‐Free Electrocatalyst. (6th September 2018) - Ghausi, Muhammad Arsalan; Xie, Jiafang; Li, Qiaohong; Wang, Xueyuan; Yang, Rui; Wu, Maoxiang; Wang, Yaobing; Dai, Liming
Abstract: Photo/electrochemical CO2 splitting is impeded by the low cost‐effective catalysts for key reactions: CO2 reduction (CDRR) and water oxidation. A porous silicon and nitrogen co‐doped carbon (SiNC) nanomaterial by a facile pyrolyzation was developed as a metal‐free bifunctional electrocatalyst. CO2 ‐to‐CO and oxygen evolution (OER) partial current density under neutral conditions were enhanced by two orders of magnitude in the Tafel regime on SiNC relative to single‐doped comparisons beyond their specific area gap. The photovoltaic‐driven CO2 splitting device with SiNC electrodes imitating photosynthesis yielded an overall solar‐to‐chemical efficiency of advanced 12.5 % (by multiplying energy efficiency of CO2 splitting cell and photovoltaic device) at only 650 mV overpotential. Mechanism studies suggested the elastic electron structure of −Si(O)−C−N− unit in SiNC as the highly active site for CDRR and OER simultaneously by lowering the free energy of CDRR and OER intermediates adsorption. Abstract : Si‐ und N‐dotierter poröser pyrolytischer Kohlenstoff ist ein effizientes Material für die CO2 ‐Reduktion und O2 ‐Erzeugung. Diese Eigenschaften könnten auf einer energetisch günstigen Adsorption von Zwischenstufen an aktiven Si(O)CN‐Zentren beruhen. Der metallfreie Elektrokatalysator bewirkte die neutrale photovoltaische CO2 ‐Spaltung mit einem Wirkungsgrad von 12.5 % für die Umwandlung von Sonnenenergie in chemische Energie.